2004
DOI: 10.1101/lm.80004
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mechanisms of Extinction of the Classically Conditioned Eyeblink Response

Abstract: It is well established that the cerebellum and its associated circuitry are essential for classical conditioning of the eyeblink response and other discrete motor responses (e.g., limb flexion, head turn, etc.) learned with an aversive unconditioned stimulus (US). However, brain mechanisms underlying extinction of these responses are still relatively unclear. Behavioral studies have demonstrated extinction as an active learning process distinct from acquisition. Experimental data in eyeblink conditioning sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 100 publications
1
40
0
1
Order By: Relevance
“…Few studies have examined the neural substrates of extinction of dEBC (Medina et al 2002;Robleto et al 2004). A computer simulation of the cerebellum suggests that the LTD that forms during acquisition is reversed, becoming LTP during CS-alone extinction (Medina et al 2002;Mauk and Ohyama 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the neural substrates of extinction of dEBC (Medina et al 2002;Robleto et al 2004). A computer simulation of the cerebellum suggests that the LTD that forms during acquisition is reversed, becoming LTP during CS-alone extinction (Medina et al 2002;Mauk and Ohyama 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The deficit in extinction observed in the rats with Purkinje cell loss following OX7-saporin treatment is consistent with the proposed model of extinction. Other mechanisms involved in extinction of eyeblink conditioning including contributions of the hippocampus, and feedback from motor and sensory nuclei in the brain stem (Robleto et al 2004) may have their effects on CR inhibition by influencing Purkinje cells' synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…CRs gradually decrease to baseline levels over the course of CS-alone extinction trials, and findings in adult subjects from a number of preparations, including Pavlovian fear and eyeblink conditioning, indicate that extinction is new, inhibitory learning rather than erasure of original learning (Napier et al 1992;Medina et al 2001;Bouton 2004;Robleto et al 2004). Fear conditioning studies in developing rats have shown that extinction at P24 or 25 leads to new learning, consistent with that seen in adult studies, whereas extinction at P17 or 18 may lead to erasure of original learning (Kim and Richardson 2010a).…”
mentioning
confidence: 99%